Short Communication: Diversity of duckweed (Araceae-Lemnoideae), morphological characteristics and its potentials as food sources for herbivorous fishes in West Java, Indonesia - YULI ANDRIANI; BUDI IRAWAN; ISKANDAR ISKANDAR; IRFAN ZIDNI; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Andriani Y, Irawan B, Iskandar, Zidni I, Partasasmita R. 2019. Diversity of duckweed (Araceae-Lemnoideae), morphological characteristics and its potentials as food sources for herbivorous fishes in West Java, Indonesia. Biodiversitas 20: 1617-1623. Duckweed is aquatic plant potential as a source of protein to feed herbivorous fish. The purpose of this study was to explore the diversity of duckweed species occurred in several areas in West Java. The exploration was done by collecting duckweed (Araceae) from water bodies such as lakes and ponds located in the fishery center in Garut, Bandung, Sumedang and Tasikmalaya Districts. The sample was identified using stereomicroscope to know the morphological characteristic. Characteristics being observed included root tip and sheath as well as the morphological frond characteristics. The result of study showed there were three species of duckweed recorded at the studied areas in West Java, namely Spirodela polyrhiza (L.) Schleid, Lemna perpusilla Torr. and Lemna gibba L. The three duckweed species can be distinguished based on its morphological characteristics, such as the number of roots, types of root tip, root sheath, symmetric-frond, gibbous-frond, and nerve-frond. In the studied areas, duckweed plants were found in ponds, stagnant water, and rice fields. Duckweeds can be used as a source of protein in fish feed as they have high protein content and complete amino acids.